2010
DOI: 10.1007/s00423-010-0687-1
|View full text |Cite
|
Sign up to set email alerts
|

Totally endoscopic lateral parathyroidectomy: prospective evaluation of 200 patients

Abstract: Totally endoscopic lateral approach can be proposed in more than half of the patients with good immediate results. Conversion rate remains important and may explain low acceptance rate of this technique.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
30
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 20 publications
0
30
0
1
Order By: Relevance
“…However, literature review and international surveys have also shown that most common approaches for minimally invasive parathyroidectomy correspond in fact to open focal mini-incision (about 70%), followed by videoassisted approach (about 20%), and totally endoscopic approach (about 10%) (1,3,7,12). Procedures that imply the utilization of the endoscope (totally endoscopic and videoassisted techniques) take advantage not only of the targeted approach, but also of the endoscopic magnification that allows performing the same intervention through a very minimal incision (7,10).…”
Section: Endoscopic Parathyroidectomy Without Robotic Systemmentioning
confidence: 99%
See 3 more Smart Citations
“…However, literature review and international surveys have also shown that most common approaches for minimally invasive parathyroidectomy correspond in fact to open focal mini-incision (about 70%), followed by videoassisted approach (about 20%), and totally endoscopic approach (about 10%) (1,3,7,12). Procedures that imply the utilization of the endoscope (totally endoscopic and videoassisted techniques) take advantage not only of the targeted approach, but also of the endoscopic magnification that allows performing the same intervention through a very minimal incision (7,10).…”
Section: Endoscopic Parathyroidectomy Without Robotic Systemmentioning
confidence: 99%
“…Carbon dioxide is insufflated at a pressure of 8 mmHg to expand the artificial space, and dissection is performed with 3-mm instruments ( Figure 1). During the procedure, identification of the recurrent laryngeal nerve and the ipsilateral parathyroid are often easily possible (3,7,15).…”
Section: Endoscopic Parathyroidectomy Without Robotic Systemmentioning
confidence: 99%
See 2 more Smart Citations
“…Besides the original description ( [11] Langenbecks Arch Surg) a large single-centre series using the totally endoscopic lateral approach for selective, minimally invasive parathyroidectomy, showing good postoperative shortterm results with a high rate (28%) of conversion to open exploration, is presented ( [6] Langenbecks Arch Surg, this issue)…”
mentioning
confidence: 99%